1988
DOI: 10.1111/j.1432-1033.1988.tb13730.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNAs for canavalin and concanavalin A from Canavalia gladiata seeds

Abstract: By a method of Escherichia coli expression‐vector‐primed cDNA synthesis, a cDNA expression library was constructed from total poly(A)‐rich RNA that was prepared from immature embryos of Canavalia gladiata. Essentially full‐length cDNA clones for two seed proteins, canavalin and concanavalin A, were selected from the library by immunological screening of the colonies and in vitro RNA synthesis and translation. The complete amino acid sequence of canavalin was determined from the nucleotide sequence of the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…For the amino acid sequence comparison of the Diocleinae lectins, the amino acid sequences of Con A (Jones, D.H., EMBL ID CECONA1, EMBL AC X01632), ConG from C. gladiata (Yamauchi et al 1989), ConL from C. lineata (Fujimura et al 1993), ConM from C. maritima (Perez et al 1991), ConV from C. virosa (Fujimura et al 1993), DGL from D. grandilfora (Richardson et al 1984) and DLL from D. lehmanni (Perez et al 1991) were taken from the corresponding references. The amino acid sequence alignments were carried on a MicroVAX 3100 (Digital, Evry, France) using the Ialign program of PIR/NBRF (Washington, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the amino acid sequence comparison of the Diocleinae lectins, the amino acid sequences of Con A (Jones, D.H., EMBL ID CECONA1, EMBL AC X01632), ConG from C. gladiata (Yamauchi et al 1989), ConL from C. lineata (Fujimura et al 1993), ConM from C. maritima (Perez et al 1991), ConV from C. virosa (Fujimura et al 1993), DGL from D. grandilfora (Richardson et al 1984) and DLL from D. lehmanni (Perez et al 1991) were taken from the corresponding references. The amino acid sequence alignments were carried on a MicroVAX 3100 (Digital, Evry, France) using the Ialign program of PIR/NBRF (Washington, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the N-terminal amino acid sequence indicated that the protein consisted of the sequence His-Ser-Gly-HisSer-Gly-Gly-Glu-Ala-Glu-, which was identical to the N-terminal sequence of sword bean canavalin matured through the removal of the N-terminal signal sequence region comprising the amino acid residues from Met 1 to Ala 26 . 17) In addition, the molecular weight of sword bean canavalin is estimated to be approximately 47.6 kDa from the primary sequence. Thus, our results suggested that sword bean canavalin was precipitated from the crude extract following addition of magnesium chloride.…”
Section: Magnesium Chloride-dependent Precipitate Formation At Varioumentioning
confidence: 99%
“…6). Although the Con A and canavalin genes are expressed at high levels in immature seeds of C. gladiata [38], Con A::GUS and canavalin-::GUS were expressed at lower levels than CaMV 35S::GUS in the transient expression (Fig. 3).…”
Section: Difference In Expression Of Con a And Canavalin Genesmentioning
confidence: 99%
“…We previously studied the synthesis and accumulation of Con A and canavalin during development of Canavalia gladiata seeds, and showed that these two proteins amounted to about 25 ~o each of the total protein in the mature seed [37]. Although the level of mRNA for both proteins reached a peak about 40 days after flowering (DAF) in the middle stage of maturation, some difference was observed in time-course change in the level and this seemed to cause the difference in the synthesis and accumulation of the two proteins [38]. The gene for Con A contains no introns and that for canavalin consists of 5 introns and 6 exons [36,39].…”
Section: Introductionmentioning
confidence: 99%